DEPRESI DAN PENANGANANNYA PADA MAHASISWA - Efa Yuliza (STAI Hubbulwathan Duri, 2015)
Depression of students in University is a group of clinical disorders characterized by loss of feeling of control and subjective experience suffering severe symptoms that appear like sadness, hopelessness, feelings of worthlessness and guilt, withdrawal from others, eating disorders, sleep disorders, withdrawal, loss of concentration, the idea of jumping up and down, tense, loss of energy and the emergence of suicidal thoughts or ideas. signs of depression in general is the existence of sadness, anxiety, loss of response to excitement, reduced or loss of feeling in love with someone else, the loss of connection and an emotional attachment premises of others, the emergence of thoughts deviate towards self-evaluation itself bad, distorted body image as well as the negative expectations of the future, inability to make decisions, the incidence of death wishes or ideas themselves and the increased dependence on others. The signs are grouped in symptoms of emotional or affective, motivational symptoms, cognitive symptoms, as well as behavioral and vegetative symptoms. Several attempts were made in the treatment of depression among the. Psychodynamic therapy, cognitive and behavioral therapy, cognitive therapy-based mindset, Social Skills Training and Activities Behavioral Therapy